the left side:
(5-xi)(y+i) = 5y + 5i - xyi -
x`i^2`
But `i^2` = -1
(5-xi)(y+i) = 5y + x + i(5
- xy)
Now, we'll equate the real parts from both
sides:
5y + x = 10 => x = 10 - 5y
We'll
equate the imaginary parts from both sides:
5 - xy = 4 => -xy
= 4-5 => xy = 1
(10-5y)y = 1
We'll remove
the brackets:
10y - `5y^2` - 1 = 0
`5y^2 - 10y +
1` = 0
We'll apply quadratic formula:
y1 = (10 +
` sqrt(100 - 20) `)/10
y1 = (10+ 4`sqrt5` )/10
y1
= `(5+2sqrt5)/5`
y2 = `(5 - 2sqrt5)/5`
x1 =10 -
5y1 => x1 = `5 - 2sqrt5`
x2 =
`5+2sqrt5`
Therefore, the values of x and y
are: x1 = `5-2sqrt5` ; y1 = `(5+2sqrt5)/5` ; x2 = `5+2sqrt5` ; y2 = `(5-2sqrt5)/5`
.
No comments:
Post a Comment